#32: Quality Improvement Strategies in the Management of Fever in Children with Cancer in a Third-level Hospital in Bolivia. (26th March 2021) - Estrada, A; Cornejo, V; Mukkada, S; Villegas, C A; Vazquez, M; Rodriguez-Auad, J P
Abstract: Background: The care of children with cancer requires systematic and standardized management to avoid complications associated with treatment, one of which is infection. Fever is an important sign of infection in a neutropenic patient and requires early management to avoid unfavorable outcomes. Many factors contribute to delays in recommended steps of fever management. The objective of this project was to measure the delay times associated with key steps in fever management and identify challenges and opportunities to improve this care process. Methods: A prospective quality improvement project was initiated between June and November 2019 at the 25-bed oncology service of the Dr. Ovidio Aliaga Uria Children's Hospital in La Paz. A data collection sheet was constructed and implemented including times for fever identification, blood culture collection, antibiotic order, and antibiotic administration. In parallel, we worked with the health personnel of this unit to deconstruct the process of fever management using block and flow diagrams. We jointly constructed an impact/effort matrix to prioritize key interventions. These interventions were developed to be implemented to improve this process. Results: During these 6 months, data from 29 neutropenic patients who had a fever was collected. The average time elapsed from fever identification until blood culture collection was 4.9 hours ( n = 28), time elapsed from fever to antibiotic initiation was 7.3 hours ( n = 27), time between antibiotic order and administration was 1.6 hours ( n = 26), and time between blood culture collection and antibiotic administration was 2.3 hours ( n = 26). The interventions proposed through the effort/impact matrix as low effort and of high impact were: priority attention of pediatric oncology patients in the emergency department through the implementation of a patient identification card to expedite the admission process, development of a fever management flowchart with a record of action schedule and improve the availability of bottles for blood culture. Conclusions: Our results demonstrate that delays exist in the management of fever in children with cancer in our hospital. Identifying the gaps and pivotal steps in the process, and opportunities for improvement are the first key steps toward implementing strategies to improve the quality of care. Categorization, testing, and execution of standardized interventions will help to improve fever management and must be done as a collaborative effort between departments involved in pediatric neutropenic patient care such as infectious diseases, pediatrics, and oncology. Our next steps include (1) training of medical and nonmedical staff involved in the admission and discharge processes to implement the patient identification card distribution and usage, (2) improving interdepartmental communication, and (3) identification of new opportunities for quality improvement to be tested and implemented.